Indole-3-acetic acid attenuates the fungal lesions in infected potato tubers - Terrile, Maria Cecilia (2006)
In this report, we demonstrated that potato tubers pre-treated with 100 μM of indole-3-acetic acid (IAA) and then inoculated with Fusarium solani f. sp. eumartii (F. eumartii) showed a decrease in the fungal lesion compared with non-IAA pre-treated and inoculated tubers. Consequently, we tested the addition of different concentrations of IAA on the fungal growth and on the proteolytic activity when the fungus was grown in liquid culture medium. Fungal growth did not change under different phytohormone concentrations, but the activity of Fusarium extracellular serine protease (FESP) clearly decreased. The inhibition of FESP activity by IAA was dose dependent. Moreover, FESP as well as others extracellular pectinolytic activities detected in IAA pre-treated and inoculated tubers decreased compared with controls. In addition, the ability of IAA production by F. eumartii was tested, and the role of IAA on potato-F. eumartii interaction is discussed.